2021
DOI: 10.1186/s12931-021-01783-z
|View full text |Cite
|
Sign up to set email alerts
|

Family with sequence similarity 13 member A mediates TGF-β1-induced EMT in small airway epithelium of patients with chronic obstructive pulmonary disease

Abstract: Background To explore the role of family with sequence similarity 13 member A (FAM13A) in TGF-β1-induced EMT in the small airway epithelium of patients with chronic obstructive pulmonary disease (COPD). Methods Small airway wall thickness and protein levels of airway remodeling markers, EMT markers, TGF-β1, and FAM13A were measured in lung tissue samples from COPD and non-COPD patients. The correlations of FAM13A expression with COPD severity and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…TGF-β1 is a key growth factor involved in inducing inflammatory processes and EMT. TGF-β1 is upregulated in the airway epithelium of individuals with chronic obstructive pulmonary disease and induces the EMT in BEAS-2B cells (Zhu et al, 2021). In this study, PRDX1 was found to be involved in regulating the LPS-and TGF-β1-induced proliferation, EMT, and collagen synthesis in airway epithelial cells.…”
Section: Discussionmentioning
confidence: 50%
“…TGF-β1 is a key growth factor involved in inducing inflammatory processes and EMT. TGF-β1 is upregulated in the airway epithelium of individuals with chronic obstructive pulmonary disease and induces the EMT in BEAS-2B cells (Zhu et al, 2021). In this study, PRDX1 was found to be involved in regulating the LPS-and TGF-β1-induced proliferation, EMT, and collagen synthesis in airway epithelial cells.…”
Section: Discussionmentioning
confidence: 50%
“…The enrolled patients were divided into two groups: In the present study, lung resection specimens from patients with COPD (COPD) ( n = 7) and non-COPD control subjects (Normal) ( n = 6). Patients were diagnosed based on the Global Initiative for Chronic Obstructive Lung Disease (GOLD) ( Guo et al, 2018 ; Zhu et al, 2021 ). The characteristics of the participants are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…These resected tissues were at least 3 cm from the tumor margin. 29 The resected samples were immediately frozen in liquid nitrogen and stored at −80°C. All patients with COPD were diagnosed according to the GOLD guideline.…”
Section: Methodsmentioning
confidence: 99%